System of responsibilities for the use of artificial intelligence. A comprehensive approach - Mercader Uguina, Jesús R. (LABOS Revista de Derecho del Trabajo y Protección Social, 2024)
The objective of this article is to provide an overview of the regulatory model that has inspired the new regulations on AI and its relations with the specific regulatory framework on occupational risk prevention. The aim is to delve deeper into the general obligations of AI system providers and the specific obligations, in terms of occupational risk prevention, of such providers and of the employer who incorporates such systems into the workplace. An analysis is also made of the current regime regarding liability for damages, with the aim of raising the range of possibilities of claims by the worker who suffers damages derived from AI and its relationship with the general regime of liability of the employer.
Keywords: System of liability; Artificial Intelligence systems; sanctions; restorative subsystem